2020
DOI: 10.30918/aerj.82.20.039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of sports expectation and environmental factors on athlete satisfaction in adolescents

Abstract: This study has been designed to evaluate the effect of the sports expectation of adolescents participating in summer sports schools in Konya and the environmental factors on athlete's satisfaction. A total of 458 individuals, 179 girls and 279 boys, who attended sports schools, participated in the study with the principle of voluntary participation via the convenience sampling method. In addition, a survey form created by conducting expert opinion and literature review was used for the relationship between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Adolescence is defined as the time between childhood and adulthood. It covers the time span between 11 and 18–20 years, and it is associated, among others, with large changes in individual behaviours (Er, 2020 ). Especially the changes between adolescences and adulthood are important because they can influence behaviour till late adulthood (Corder et al, 2019 ).…”
Section: Exercise-related Outcome Expectancies and Sport Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescence is defined as the time between childhood and adulthood. It covers the time span between 11 and 18–20 years, and it is associated, among others, with large changes in individual behaviours (Er, 2020 ). Especially the changes between adolescences and adulthood are important because they can influence behaviour till late adulthood (Corder et al, 2019 ).…”
Section: Exercise-related Outcome Expectancies and Sport Behaviourmentioning
confidence: 99%
“…Studies showed that the predictors of sports behaviour change with age (Sterdt et al, 2014 ) as well as the reasons for participating in sports (Brown et al, 2017 ). Moreover, some studies report age differences, while others do not (Er, 2020 ).…”
Section: Exercise-related Outcome Expectancies and Sport Behaviourmentioning
confidence: 99%